The Hidden Curriculum in Ethics and its Relationship to Professional Identity Formation: A Qualitative Study of Two Canadian Psychiatry Residency Programs - Gupta, Mona; Forlini, Cynthia; Laneuville, Laurence (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2020)
The residency years comprise the last period of a physician’s formal training. It is at this stage that trainees consolidate the clinical skills required for independent practice and achieve a level of ethical development essential to their work as physicians, a process known as professional identity formation (PIF). Ethics education is thought to contribute to ethical development and to that end the Royal College of Physicians and Surgeons of Canada (RCPSC) requires that formal ethics education be integrated within all postgraduate specialty training programs. However, a formal ethics curriculum can operate in parallel with informal and hidden ethics curricula, the latter being more subtle, pervasive, and influential in shaping learner attitudes and behavior. This paper reports on a study of the formal, informal, and hidden ethics curricula at two postgraduate psychiatry programs in Canada. Based on the analysis of data sources, we relate the divergences between the formal, informal, and hidden ethics curricula to two aspects of professional identity formation (PIF) during psychiatry residency training. The first is the idea of group membership. Adherence to the hidden curriculum in certain circumstances determines whether residents become part of an in-group or demonstrate a sense of belonging to that group. The second aspect of PIF we explore is the ambiguous role of the resident as a student and a practitioner. In ethically challenging situations, adherence to the messages of the hidden curriculum is influenced by and influences whether residents act as students, practitioners, or both. This paper describes the hidden curriculum in action and in interaction with PIF. Our analysis offers a complementary, empirical perspective to the theoretical literature concerning PIF in medical education. This literature tends to position sound ethical decision-making as the end result of PIF. Our analysis points out that the mechanism works in both directions: how residents respond to hidden curriculum in ethics can be a driver of professional identity formation.